2007
DOI: 10.1158/0008-5472.can-06-1962
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Mantle Lymphoma Tumor Establishment by Routing Transferrin Receptor toward Lysosomal Compartments

Abstract: Mantle cell lymphoma (MCL) is one of the most frequent of the newly recognized non-Hodgkin's lymphomas. The major problem of MCL therapy is the occurrence of relapse and subsequent resistance to chemotherapy and immunotherapy in virtually all cases. Here, we show that one injection of antihuman transferrin receptor (TfR) monoclonal antibody A24 totally prevented xenografted MCL tumor establishment in nude mice. It also delayed and inhibited tumor progression of established tumors, prolonging mice survival. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…On the assumption that TfR accompanied the streptavidin conjugate during vesicular transport, this suggests that some TfR was not recycled but was routed to lysosomes. Routing of TfR to lysosomes has been reported in certain circumstances (34,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the assumption that TfR accompanied the streptavidin conjugate during vesicular transport, this suggests that some TfR was not recycled but was routed to lysosomes. Routing of TfR to lysosomes has been reported in certain circumstances (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…5). Initially, the fibroblasts were incubated for 17 h in medium containing 35 SO 4 , and the labeled GAG was examined at the end of that period. The accumulation of 35 SO 4 -GAG in the Idua Ϫ/Ϫ cells was greatly elevated over normal (data not shown).…”
Section: Endocytosis and Functionality Of Aptamer Conjugate Of A Lysomentioning
confidence: 99%
“…Inhibition of holo-Tf binding seems to be not required for antibody cytotoxicity because, whereas IgG-A24 (17) and IgA-42/6 (9) inhibited holo-Tf binding (by a competitive and a noncompetitive mechanism, respectively), avidin-fused IgG3 (12) and IgM-R17208 (11) did not. Notably, IgG-A24 and avidin-fused-IgG3 reduced TfR expression by impairing TfR recycling to the cell surface and routing the internalized TfR to the lysosomal degradation pathway (15,18).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, low expression of TfR1 is seen in epithelial cells of various organs. 13,36 Human studies have confirmed that TfR1 expression is higher in proliferating normal and malignant transformed cells than in their resting counterparts 42,44 and that TfR1 expression correlates with a variety of proliferation markers, including mitotic index, 31 Ki67 expression, 24 and 3 H-thymidine incorporation. 21 TfR1 expression has been measured and found to be expressed in many hematopoietic and nonhematopoietic neoplasms in humans, including non-Hodgkin lymphoma (NHL), 11,13,15,17,21,25,34,47 acute leukemia, 3 and solid tumors of the brain, bladder, liver, and gastrointestinal tract.…”
mentioning
confidence: 94%
“…17,21 Given the high expression of TfR1 on neoplastic cells, many investigators have pursued it as an oncolytic target through the use of a variety of strategies including monoclonal antibodies, with or without conjugation to cytotoxic substances, as well as toxic small molecules which use the TfR1 to enter the cell. 3,4,6,7,24,27,29 Phase 2 clinical trials of one such treatment for human NHL-gallium nitrate-have shown promise in patients who have relapsed after standard chemotherapy. Some patients developed anemia during treatment; otherwise, the drug was well tolerated.…”
mentioning
confidence: 99%